PENERIMAAN DIRI DAN SIKAP PERCAYA DIRI PADA ANAK SEKOLAH DASAR - Ornella Alika; Arri Handayani; Dini Rakhmawati (STKIP Subang, 2024)
Self-acceptance is very important in the development of students, it is often found that elementary school students have not fully accepted the strengths, weaknesses, and unique things that exist in themselves, thus making children experience low self-esteem and decreased self-confidence in students. This article was compiled with a literature study of 6 articles with vulnerable years 2018-2023 and relevant previous reading sources. The results of the literature review found that self-acceptance and self-confidence in elementary school children are very important and interrelated.